2013
DOI: 10.1094/mpmi-07-12-0188-r
|View full text |Cite
|
Sign up to set email alerts
|

Gene-for-Gene Tolerance to Bacterial Wilt in Arabidopsis

Abstract: Bacterial wilt caused by Ralstonia solanacearum is a disease of widespread economic importance that affects numerous plant species, including Arabidopsis thaliana. We describe a pathosystem between A. thaliana and biovar 3 phylotype I strain BCCF402 of R. solanacearum isolated from Eucalyptus trees. A. thaliana accession Be-0 was susceptible and accession Kil-0 was tolerant. Kil-0 exhibited no wilting symptoms and no significant reduction in fitness (biomass, seed yield, and germination efficiency) after inocu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…One study found evidence of a GFG like interaction for tolerance to bacterial wilt in Arabidopsis conferred by a single R‐gene (Van der Linden et al. ), but such specificities might also be effectively modeled by a tolerance range function. Overall, however, our results have emphasized that whatever the model structure, the coevolutionary interaction of hosts and parasites is not in itself enough to generate diversity in host tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…One study found evidence of a GFG like interaction for tolerance to bacterial wilt in Arabidopsis conferred by a single R‐gene (Van der Linden et al. ), but such specificities might also be effectively modeled by a tolerance range function. Overall, however, our results have emphasized that whatever the model structure, the coevolutionary interaction of hosts and parasites is not in itself enough to generate diversity in host tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…In A. thaliana, the study of the interaction between two ecotypes, Nd-1 and Kil-0, and two strains of R. solanacearum, GMI1000 and BCCF402 (both phylotype I strains), respectively, revealed the involvement of RRS1-R. RRS1-R, a Toll/interleukin-1 receptor-nucleotide-binding siteleucine-rich repeat (TIR-NBS-LRR) gene with a WRKY C-terminal domain, has been described as a single recessive resistance gene against strain GMI1000, through the direct recognition of the PopP2 effector (Deslandes et al, 1998(Deslandes et al, , 2003. Interestingly, it has been demonstrated recently that the gene-for-gene interaction RRS1-R-PopP2 is also involved in Kil-0 tolerance ( Van der Linden et al, 2013). Indeed, Kil-0 does not exhibit wilting symptoms after its inoculation with strain BCCF402 of R. solanacearum, despite a high bacterial multiplication in planta.…”
Section: Complex Mechanisms Underlie Bacterial Wilt Resistance and Tomentioning
confidence: 99%
“…However, since the molecular basis of resistance to GLS has not been characterized yet, it still remains possible that quantitative resistance could be effected by so-called weak resistance (R) genes that recognize pathogen effectors in a gene-for-gene manner [18]. A mechanism for this could be tolerance mediated through an R gene, as was recently shown in Arabidopsis pathosystems [19,20]. …”
Section: Introductionmentioning
confidence: 99%